Korelasi antara jumlah mikronukleus dan ekspresi 8-oxo-dG akibat paparan radiografi panoramic (The correlation of micronucleus formation and 8-oxo-dG expression due to the panoramic radiography exposure) - Rurie Ratna Shantiningsih; Suwaldi Suwaldi; Indwiani Astuti; Munakhir Mudjosemedi (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: The expression of 8-oxo-dG is defined as one form of damaged DNA occuring as the result of oxidation reaction due to X ray exposure. Panoramic radiography exposure has been widely known to be able to increase micronucleus which are signing the early stage and as biomarker in carsinogenesis mechanism. Purpose: The purpose of this research was to determine the correlation between micronucleus number and 8-oxo-dG expression as a result of panoramic radiography exposure. Methods: Twelve New Zealand male rabbits aging 6 months were divided into 4 groups. Group I were rabbits that represented 0 day, group II represented 3th day, group III represented 6th day, and group IV represented 9th day after the panoramic radiography exposure. Respectively samples were swabbed at mandibular anterior gingival mucosa before and after the panoramic radiography exposure. The swabbed samples were coloured by using Feulgen-Rossenbeck modified staining for calculating the amount of micronucleus formation. Expression of 8-oxodG was detected using immunohistochemical of rabbit’s gingival mucosa epithelium. Statistical analysis were carried out on pearson correlation. Results: There was a highest increasing of micronucleus on the 9th day after panoramic radiography exposure. Meanwhile, there was significant correlation (p=0,049) of the increasing amount of micronucleus and 8-oxo-dG expression in negatively correlation (r = -0,578). The increasing of micronucleus formation on the 9th day after panoramic radiography exposure was accordance with some previous studies. The expression score of 8-oxo-dG decreases as the day goes by. Conclusion: There was a correlation between the number of micronucleus and expression score of 8-oxo-dG.Latar belakang: Ekspresi 8-oxo-dG adalah suatu bentuk kerusakan DNA yang terjadi akibat reaksi oksidatif dari paparan sinar X. Paparan radiografi panoramik telah diketahui menyebabkan peningkatan jumlah mikronukleus yang merupakan biomarker tahap dini mekanisme karsinogenesis. Tujuan: Tujuan penelitian ini adalah untuk meneliti korelasi antara jumlah mikronukleus dan ekspresi 8-oxo-dG akibat paparan radiografi panoramik. Metode: Sebanyak 12 ekor kelinci New Zealand jantan usia 6 bulan dibagi menjadi 4 kelompok. Kelompok I merupakan kelinci untuk mewakili hari ke-0, kelompok II untuk mewakili hari ke-3, kelompok III untuk mewakili hari ke-6, dan kelompok IV untuk mewakili hari ke-9 setelah paparan radiografi panoramik. Terhadap seluruh kelinci dilakukan usapan pada mukosa gingiva anterior rahang bawah sebelum dan sesudah dilakukan paparan radiografi. Selanjutnya terhadap sampel usapan itu dilakukan pewarnaan menggunakan teknik pewarnaan modifikasi Feulgen-Rossenbeck untuk menghitung jumlah mikronukleus. Ekspresi 8-oxo-dG dinilai dari pemeriksaan imunohistokimia pada sel epitel mukosa gingiva kelinci. Analisis statistik menggunakan uji korelasi Pearson. Hasil: Peningkatan jumlah mikronukleus paling tinggi terjadi pada hari ke-9 setelah paparan radiografi panoramik. Sementara itu, terdapat korelasi yang signifikan (p=0,049) antara peningkatan jumlah mikronukleus dan ekspresi 8-oxo-dG dengan arah korelasi yang negatif (r=-0,578). Peningkatan jumlah mikronukleus yang terjadi pada hari ke-9 setelah paparan radiografi panoramik ini sesuai dengan penelitian sebelumnya. Dengan bertambahnya hari skor ekspresi 8-oxo-dG semakin menurun. Simpulan: Terdapat korelasi antara jumlah mikronukleus dan skor ekspresi 8-oxo-dG.